1993
DOI: 10.1007/bf00202489
|View full text |Cite
|
Sign up to set email alerts
|

Routine diagnosis of DiGeorge syndrome by fluorescent in situ hybridization

Abstract: In a series of ten patients affected by DiGeorge syndrome, we screened, by high resolution banding and fluorescent in situ hybridization of a cosmid probe, for microdeletions associated with this syndrome. In the ten patients, a microdeletion was demonstrated by in situ hybridization, but suspected only in two patients by high resolution banding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…Hence, as previously suggested, FISH should not be used as the only diagnostic method for 22q11.2DS. 39 The phenotypic heterogeneity in 22q11.2DS might be because of (1) the various sizes of the deletions and/or (2) rearrangements elsewhere on the genome -especially CNVs, mutations in candidate genes and changes in the three-dimensional structure of the genome that can lead to dysregulation of gene expression. Zeitz et al 40 found that longrange interactions in the COMT gene had an impact on phenotypic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as previously suggested, FISH should not be used as the only diagnostic method for 22q11.2DS. 39 The phenotypic heterogeneity in 22q11.2DS might be because of (1) the various sizes of the deletions and/or (2) rearrangements elsewhere on the genome -especially CNVs, mutations in candidate genes and changes in the three-dimensional structure of the genome that can lead to dysregulation of gene expression. Zeitz et al 40 found that longrange interactions in the COMT gene had an impact on phenotypic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent in situ hybridization was performed as previously described (37). Plasmid pPR55 was labeled with biotin-11-dUTP (Sigma) using the nick translation mix (Boehringer Mannheim) according to the supplier.…”
Section: Strainsmentioning
confidence: 99%
“…Recently, several studies have suggested that genetic and epigenetic factors exhibit a role in phenotypic variance (2,3,7). Phenotypic variability is often observed between unrelated or related individuals or twins with the same microdeletion syndrome, such as 22q11.2 (3,(8)(9)(10). Observation of the genetic history of a syndrome in MZs often leads to a greater understanding of the phenotypic variability (11).…”
Section: Introductionmentioning
confidence: 99%